Signal transduction of Helicobacter pylori during interaction with host cell protein receptors of epithelial and immune cells - Suneesh Kumar, Pachathundikandi; Tegtmeyer, Nicole; Backert, Steffen (Gut Microbes, 2013)
Helicobacter pylori infections can induce pathologies ranging from chronic gastritis, peptic ulceration to gastric cancer. Bacterial isolates harbor numerous well-known adhesins, vacuolating cytotoxin VacA, protease HtrA, urease, peptidoglycan, and type IV secretion systems (T4SS). It appears that H. pylori targets more than 40 known host protein receptors on epithelial or immune cells. A series of T4SS components such as CagL, CagI, CagY, and CagA can bind to the integrin α5β1 receptor. Other targeted membrane-based receptors include the integrins αvβ3, αvβ5, and β2 (CD18), RPTP- α/β, GP130, E-cadherin, fibronectin, laminin, CD46, CD74, ICAM1/LFA1, T-cell receptor, Toll-like receptors, and receptor tyrosine kinases EGFR, ErbB2, ErbB3, and c-Met. In addition, H. pylori is able to activate the intracellular receptors NOD1, NOD2, and NLRP3 with important roles in innate immunity. Here we review the interplay of various bacterial factors with host protein receptors. The contribution of these interactions to signal transduction and pathogenesis is discussed. © 2013 Landes Bioscience.
Created from Fastlane, Scopus look-up
Keywords: c-Met; E-cadherin; EGF receptor; Integrins; Molecular pathogenesis; Virulence